Neuroprotective effects of Danshensu in Parkinson's disease mouse model induced by 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine. Issue 1 (February 2019) - Han, Bing; Che, Xin; Zhao, Yue; Li, Cuiting; He, Jie; Lu, Yan; Wang, Zhenhua; Wang, Tian
Abstract : Parkinson's disease (PD) causes major changes in dopaminergic neurons of the brain, resulting in motor symptoms in older adults. A previous study showed that Danshensu alleviates the cognitive decline by attenuating neuroinflammation. In the present study, we investigated the neuroprotective effect of Danshensu in the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) mouse model of PD. C57BL/6 mice were randomly divided into the following four groups: control, MPTP, Danshensu at 15 mg/kg, and Danshensu at 60 mg/kg. The mice were administered Danshensu intragastrically for 14 days. In the behavioral tests, Danshensu treatment alleviated motor dysfunction induced by MPTP. The number of tyrosine hydroxylase-positive neurons in the substantia nigra was significantly reduced in the MPTP group, relative to the control group; Danshensu partially blocked this reduction in tyrosine hydroxylase-positive neurons. In addition, Danshensu attenuated the reductions in striatal dopamine and 5-HT levels induced by MPTP. Danshensu also diminished the increase in Iba1-positive cells in the substantia nigra and reduced the levels of interleukin-1β and tumor necrosis factor-α in the striatum. These findings suggest that Danshensu exerts neuroprotective effects and improves motor function in PD mice, at least in part, by reducing neuroinflammation.